Revising Large Scars - Liotta, Dara R.; Costantino, Peter D.; Hiltzik, David H. (Facial Plastic Surgery, 2012)
Large scars in the head and neck are often the cause of significant emotional distress to patients, and often present unique challenges to the plastic and reconstructive surgeon undertaking their revision. The primary goal of scar revision is to eliminate compromise of function that may have resulted from scar contracture; a secondary goal is to improve the appearance of the scar. Special techniques for the revision of large scars include serial partial excision, rapid intraoperative or prolonged tissue expansion, split- and full-thickness skin grafting, regional flaps, and free microvascular tissue transfer. Recent research has investigated the use of artificial skin and autologous fat grafting for large scar revision.
Keywords: scar revision; large scars; serial partial excision; tissue expansion; skin grafts